Promoting Covid-19 Health Protocol through Indonesian Folk Songs - Thoyib, Muhammad Edy (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2024)
Compliance with health protocols during the COVID-19 pandemic is a crucial issue. Some segments of society tend to disregard the prevailing protocols due to a lack of awareness of their importance, making efforts to instill public awareness and adherence to health protocols a significant concern during this pandemic. Among the community's various initiatives, using folk songs as a medium for conveying messages and educating the public has gained prominence. This article aims to investigate the promotion of COVID-19 health protocols through folk songs. The research employs a qualitative descriptive approach focusing on Indonesian folk songs addressing the theme of the COVID-19 pandemic, which are uploaded on YouTube. The findings indicate that Indonesian folk songs addressing COVID-19 issues articulate themes related to health protocols, social solidarity, calls for reflection, and prayers. These songs incorporate figurative language elements such as metaphors, personification, and hyperbole. The use of figurative language in these songs emphasizes content related to health, social issues, and religion. In conclusion, folk songs, in addition to providing entertainment, can convey educational messages to their listeners. Health promotion should explore creative avenues involving artists alongside conventional ways.